Accuracy of Evaluation of Fatty Liver with Third-Generation Unenhanced Dual-Energy CT and MRI: Prospective Comparison with MR Spectroscopy - S. Rajesh; Venkatesh Kasi Arunachalam; Gopinath Periaswamy; Gobi Kalyan; Rupa Renganathan; Gowtham SM; Mathew Cherian (Thieme Medical and Scientific Publishers Pvt. Ltd., 2023)
Background and Objectives The purpose of this study is to evaluate and establish the accuracy of noninvasive methods, including third-generation dual-source dual-energy computed tomography (DECT) and proton density fat (PDF) fraction on magnetic resonance imaging (MRI) using three-dimensional multiecho multipoint chemical shift-encoded spoiled gradient echo (q-Dixon) sequence in the quantification of hepatic steatosis; with H1-MR spectroscopy (MRS) as the reference standard. Materials and Methods A total of 47 patients were included in this prospective study. We studied the accuracy of fatty liver detection using third-generation DECT using mixed set images (MSIs), virtual monochromatic images (VMIs), and MRI q-Dixon. The results were compared with H1-MRS. Data were analyzed using linear regression for each technique compared with MRS. Results Our study's correlation and linear regression analysis showed a good correlation between PDF values obtained by H1-MRS and MR q-Dixon methods (r = 0.821, r 2 = 0.674, p < 0.001). On MSI, H1-MRS showed a low correlation with average liver attenuation (r 2 = 0.379, p < 0.001) and a moderate correlation with liver attenuation index (r 2 = 0.508, p < 0.001) noted. There was a moderate correlation between H1-MRS and average liver attenuation and liver attenuation index on VMI at 80 to 120 keV with r 2 = 0.434, p < 0.001, and r 2 = 0.485, p < 0.001, respectively. Conclusion MRI q-Dixon is the method of choice for evaluating fat quantification in the absence of H1 MRS. Among DECT images, VMI is valuable in the evaluation of hepatic fat as compared with the mixed set of images.